DINAMIKA PENGGUNA MEDIA SOSIAL TERKAIT CALON PRESIDEN PEMILIHAN UMUM 2024 - Samad, M. Yusuf; Pramuji, Angger; Kusnarno, Tarwo; Erry S, Hediati (Gema Kampus IISIP YAPIS Biak, 2023)
Ahead of the 2024 general election (Pemilu), a number of political parties have declared their presidential candidates. However, there are pros and cons on Twitter social media regarding Anies Baswedan’s nomination by the National Democratic Party (Nasdem). This study aims to determine the dynamics of Twitter social media users after Anies Baswedan’s declaration as a presidential candidate for RI 2024. Descriptive qualitative research methods are used in answering the problem formulation. The author uses New Media theory and Propaganda theory and is assisted by a social media analysis tool in the form of Netray Media Monitoring to analyze the dynamics of Twitter social media users. The results of the study show that the dynamics that occur are due to the pros and cons regarding Anies Baswedan’s nomination as a 2024 presidential candidate by the Nasdem Party. The pros and cons created negative sentiment and positive sentiment towards Anies which then made Anies busy being discussed on Twitter social media, causing Anies to become the most popular on Twitter social media